2009
DOI: 10.2139/ssrn.1531723
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability, Poverty and Coping in Zimbabwe

Abstract: This paper uses five life histories from three locations in Zimbabwe-one peri-urban, one urban and one rural-to provide a window on current processes of impoverishment and adverse coping. Each case and location highlight key aspects of Zimbabwe's recent economic and political turmoil. Together the cases suggest that, similar to Hoddinott's work on the persistence of the 1993-94 rainfall shock in rural Zimbabwe, above and beyond increased mortality rates and morbidity levels, current adverse forms of coping are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Many studies exist that examine relative vulnerability across countries (Webber & Rossouw, 2010), such as Turvey's (2007) composite vulnerability index (CVI) of 100 developing countries, but rarely is attention paid to the differing vulnerability of regions within these countries. At the local level, there is a large and growing body of work examining local-level vulnerability, be it at the household level (Bird & Prowse, 2008) or Cutter's place-based vulnerability indices centred upon United States Census Bureau block-groups (Cutter, Mitchell, & Scott, 2000) or later community resilience studies undertaken at the larger county level throughout coastal US states (Cutter, 2006;Cutter, Barnes, & Berry, 2008).…”
Section: Vulnerability Assessmentsmentioning
confidence: 99%
“…Many studies exist that examine relative vulnerability across countries (Webber & Rossouw, 2010), such as Turvey's (2007) composite vulnerability index (CVI) of 100 developing countries, but rarely is attention paid to the differing vulnerability of regions within these countries. At the local level, there is a large and growing body of work examining local-level vulnerability, be it at the household level (Bird & Prowse, 2008) or Cutter's place-based vulnerability indices centred upon United States Census Bureau block-groups (Cutter, Mitchell, & Scott, 2000) or later community resilience studies undertaken at the larger county level throughout coastal US states (Cutter, 2006;Cutter, Barnes, & Berry, 2008).…”
Section: Vulnerability Assessmentsmentioning
confidence: 99%
“…In South Africa, no complaints have been received so far which suggests that prisoners are not getting sufficient food. However, in others countries like Zimbabwe, it has been reported through the media that prisoners are sleeping at night without having eaten since the government of the Republic of Zimbabwe is not fulfilling its responsibility of feeding them (Bird and Prowse, 2008). It has also been reported that in Zimbabwe, it is not only prisoners who are not having access to sufficient food, but also ordinary citizens ( Laakso, 1996).…”
Section: The Position Of Vulnerable Groupsmentioning
confidence: 99%
“…He attributes decline to a combination of lack of opportunity, acute shocks and chronic downward pressures such as ill health, and diminution of coping resources over the long term. Davis (2011) also identifies destructive coping strategies such as sale or mortgaging of land which diminish people's ability to move out of poverty in the future (see also Bird and Prowse, 2009 who address impoverishment and adverse coping using five life histories from three locations in Zimbabwe). Kothari and Hulme's (2004) smaller-scale study in rural Bangladesh (n=42 households) focused on poverty maintainers, identifying gaps in state, market, civil society, and family support that locked households into poverty by preventing asset accumulation.…”
Section: Literature Reviewmentioning
confidence: 99%